SSS-class revival hunter. 01 - Sinnoa; Neida (Ize Press, 2024)
"Some people are born lucky, chosen to receive power and riches beyond imagination, but Gongja Kim? He's a total loser with a completely useless ability: duplicating others' skills--that is, after they kill him. Gongja's all but given up...until he witnesses the strongest hunter in the world and his idol, Flame Emperor, committing murder and is slaughtered in cold blood! But who knew his former idol was hiding just the skill he needed to turn his fortune around? Now practically unstoppable, Gongja sets out to take revenge and climb his way to the top!"--